Does providing childcare to unemployed affect unemployment duration? - Ulrika Vikman (Uppsala University, Department of Economics, 2010)
This paper examines if the probability of leaving unemployment changes for unemployed parents with young children when childcare is available. To investigate this, I use the heterogeneity among Swedish municipalities before the implementation of a 2001 Swedish childcare reform making it mandatory for municipalities to offer childcare to unemployed parents for at least 15 hours per week. In the study difference-in-differences and difference-in-difference-indifferences methods are used. The results indicate a positive effect on the probability of leaving unemployment for mothers when childcare is available, but no effect is found for fathers. For mothers, some heterogeneous effects are also found, with a greater effect on the probability of leaving unemployment for work when childcare is available for mothers with only compulsory schooling or university education and mothers with two children.
urn:nbn:se:uu:diva-126128
Keywords: J13; J64; 330; Unemployment duration; Childcare; Kinderbetreuung; Arbeitslosigkeit; Dauer; Wirkungsanalyse; Schweden